A Semiotic Analysis of Diary of a Wimpy Kid Movie Posters - Amri, Ulil; Pratiwi, Anne (Vivid: Journal of Language and Literature, 2023)
This research is a descriptive qualitative research on semiotic field. The subiect of this research is a poster series of Diary of a Wimpy Kid, a movie adaptation of the same title semi-animated children book by Jeff Kinney. The data consists of a teaser poster and a theatrical poster of the movie film derived from Cinemags Movie Magazine and 20th Century Fox. This research aims to analyze semiotic signs from both posters by identifying icon, index, symbol, code, language, and myth following Saussure's, Peirce's, Danesi's, and Barthe's theories on Semotics. The result of the analysis presented 8 semiotic signs (4 on each poster) with the detailed analysis of signs, icon, index, symbol, code, and myth on each signs.